Research of competitive environment of Klaipėda Seaport comparing to other seaports in the eastern Baltic Sea region - Jarašūnienė, Aldona; Greičiūnė, Laima; Šakalys, Algirdas (Transport, 2012)
Constructive and systematic management of a seaport may determine its successful competitive ability in the international market. The analysis of competitive ability of Klaipėda Seaport highlighted its weakest points, influencing the overall competitiveness of the port. The encouragement of port competitive ability is often stressed, however, there is a lack of methodologically based competitive models that include all key factors determining port competitive ability. The current paper gives stages of evaluation both the significance of indices and the importance of criteria in the international market allowed us to determine factors that have an impact on port competitive ability mostly. The method, allowing to predict cargo flows, was used in the description of scenarios for the encouragement of port competitiveness. In order to ensure these cargo flows the port development is also concerned, as an integrated task, which would allow the evaluation of possible changes of cargo flows, port investments and influence of other ports on cargo flows, etc. First Published Online: 30 Mar 2012